OPTIMIZATION OF WASTE BANK AND MAGGOT CULTIVATION AS A SOLUTION TO ENVIRONMENTAL CONSERVATION BASED ON THE PRINCIPLE OF HIFDZUL BI'AH - Nurullah, Ahmad Rizkhan; Abidin, Zainul; Ramadhan, Novia (JOURNAL OF ISLAMIC AND LAW STUDIES, 2025)
The phenomenon of environmental degradation is increasingly alarming, characterized by high pollution and poor waste management. In Indonesia, more than 65 million tons of waste are generated every year, most of which have not been managed properly. Environmental conservation concepts, such as Waste Bank and maggot cultivation, can be a solution. Waste Bank manages recycled waste, while Black Soldier Fly (BSF) maggot decomposes organic waste, produces fertilizer, and reduces waste volume. The principle of hifdzul bi'ah in Islam supports this effort to maintain the balance of nature and improve the quality of life. This research uses a qualitative method that is a literature study. After being analyzed through the study of relevant literature, the author then classifies based on the subtitles contained in the discussion points. The results of this study show that the application of the principle of hifdzul bi'ah in the management of Waste Bank and maggot cultivation can be seen from the community's efforts by establishing Waste Bank, the community practices waste sorting as a form of concern for the environment in accordance with the values of hifdzul bi'ah. Similarly, the use of maggot in decomposing organic waste is not only a practical solution, but also reflects awareness of the importance of managing waste without damaging the ecosystem. This synergy has a positive impact on the environment, such as reducing waste to landfill, reducing pollution, and reducing methane emissions from organic waste.